2016
DOI: 10.1016/j.apmr.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Acute Trauma Factor Associations With Suicidality Across the First 5 Years After Traumatic Brain Injury

Abstract: Severe ECI carried a nearly 3-fold increase in the odds of SI after TBI, but it was not related to SA. Head injury severity and less severe ECI were not associated with SI or SA. These findings warrant additional work to identify factors associated with severe ECI that make individuals more susceptible to SI after TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
5
18
0
Order By: Relevance
“…19 Also, the methodology and matching criteria have been used to link data from all TBIMS centers with acute care data from the NTDB, and we generated a database that includes matched records for over 3500 individuals in the TBIMS National Database. We have used this matched dataset to examine the influence of extracranial injury on mental health outcomes, 28 and we will explore how other aspects of the acute trauma complex, comorbidities, as well as acute trauma complications and treatments, influence health care utilization and long term outcomes. The long-term goal of this work in TBI is to generate a greater insight into how heterogeneity with individual factors like comorbid burden, as well as how heterogeneity with the polytrauma complex and acute care practices, can influence recovery trajectories for individuals with moderate-to-severity TBI that receive acute rehabilitation services.…”
Section: Discussionmentioning
confidence: 99%
“…19 Also, the methodology and matching criteria have been used to link data from all TBIMS centers with acute care data from the NTDB, and we generated a database that includes matched records for over 3500 individuals in the TBIMS National Database. We have used this matched dataset to examine the influence of extracranial injury on mental health outcomes, 28 and we will explore how other aspects of the acute trauma complex, comorbidities, as well as acute trauma complications and treatments, influence health care utilization and long term outcomes. The long-term goal of this work in TBI is to generate a greater insight into how heterogeneity with individual factors like comorbid burden, as well as how heterogeneity with the polytrauma complex and acute care practices, can influence recovery trajectories for individuals with moderate-to-severity TBI that receive acute rehabilitation services.…”
Section: Discussionmentioning
confidence: 99%
“…17 A history of substance abuse prior to injury, and drug use at the time of injury, increases the odds of suicidal ideation postinjury. 20,32 A large Danish population study of TBI and suicide demonstrated that substance misuse increased suicide rates across 3 diagnostic groups representing severity of injury: concussion, cranial fracture, and cerebral contusion or traumatic intracranial hemorrhage. 36 Beyond severity of injury, substance use may be an independent risk factor for suicidality.…”
mentioning
confidence: 99%
“…The importance of early identification of mTBI/concussion is a significant concern, as untreated concussions can contribute to morbidity with potentially debilitating and lingering post-concussive symptoms (including cognitive impairment, development of depression and anxiety, and somatization disorder). 31,32 Additionally, in athletes there is a higher incidence of repeat concussion following a first concussion and an increase chance for worse injury if an athlete is allowed to return to play prior to symptom resolution. 33,34 This head-injured normal validation study demonstrated as a secondary end-point, the potential clinical utility of the EEG BFI in providing important quantitative information about the status of brain function in mTBI relative to an uninjured normal population at the initial point of triage in the emergency setting.…”
Section: Eeg Biomarker Of Brain Function Impairment In Tbi Discussionmentioning
confidence: 99%